Ageing, physical activity, recreation and wellbeing - Humberstone, Barbara (Cambridge Scholars Publishing, 2016)
This book will serve to raise awareness of ways of healthy ageing that are facilitated by different forms of, and approaches to, physical activity, exercise and recreation. It presents a collection of studies focusing on the effectiveness of different methods that promote an active lifestyle among communities and older people in general. The contributions draw upon qualitative and quantitative paradigms that have 'active ageing' at the core of their investigations. The book imparts knowledge about recent advances in physical activity, recreation and wellbeing initiatives that will benefit the.